Martín Luis Guzmán Ferrer. La inflación y el desarrollo en América Latina. México : Universidad Nacional Autónoma de México, 1976. 653 p. - Méndez Villarreal, Sofía (El Colegio de México A.C., 1977)
Martín Luis Guzmán Ferrer, La inflación y el desarrollo en América Latina, México, Universidad Nacional Autónoma de México, 1976.